“Partisipasi Politik Narapidana Lembaga Pemasyarakatan Kelas IIA wanita Kota Semarang dalam Pemilihan Walikota Semarang periode 2015-2020 - Yudha Nursandi Pratama; Purwoko .; Puji Astuti (Journal of Politic and Government Studies, 2016)
The importance of political participation which does not discriminate where people are can be shown in the political participation of the convicts in women’s correctional facility II A Semarang in mayor of Semarang election. The background of this research is the political participation of the convicts in mayor election. Research type that is used is qualitative – analytic descriptive, a method that tells and paraphrases the available data. The purpose of this research is to explain the political participation of the convicts inside and outside the correctional facility in the mayor election based on the facts found during the research. However, with all the limitation, the convicts were willing to participate in the mayor election and understood what political participation was. Limited information did not diminish the enthusiasm of the convicts in the election process. This should be watched by the government in order to equalize the right of the society to get information. Socialization and guidance needs to be given by the government to increase the quality of political participation of the convicts inside the correctional facility. Keywords: political participation; convict; correctional facility; mayor election